Pharmacy‐based management for depression in adults - Brown, Jennifer Valeska Elli (Cochrane Database Syst Rev, 2019)
BACKGROUND: It is common for people not to take antidepressant medication as prescribed, with around 50% of people likely to prematurely discontinue taking their medication after six months. Community pharmacists may be well placed to have a role in antidepressant management because of their unique pharmacotherapeutic knowledge and ease of access for people. Pharmacists are in an ideal position to offer proactive interventions to people with depression or depressive symptoms. However, the effectiveness and acceptability of existing pharmacist‐based interventions is not yet well understood. The degree to which a pharmacy‐based management approach might be beneficial, acceptable to people, and effective as part of the overall management for those with depression is, to date, unclear. A systematic review of randomised controlled trials (RCTs) will help answer these questions and add important knowledge to the currently sparse evidence base. OBJECTIVES: To examine the effects of pharmacy‐based management interventions compared with active control (e.g. patient information materials or any other active intervention delivered by someone other than the pharmacist or the pharmacy team), waiting list, or treatment as usual (e.g. standard pharmacist advice or antidepressant education, signposting to support available in primary care services, brief medication counselling, and/or (self‐)monitoring of medication adherence offered by a healthcare professional outside the pharmacy team) at improving depression outcomes in adults. SEARCH METHODS: We searched the Cochrane Common Mental Disorders Controlled Trials Register (CCMD‐CTR) to June 2016; the Cochrane Library (Issue 11, 2018); and Ovid MEDLINE, Embase, and PsycINFO to December 2018. We searched theses and dissertation databases and international trial registers for unpublished/ongoing trials. We applied no restrictions on date, language, or publication status to the searches.  SELECTION CRITERIA: We included all RCTs and cluster‐RCTs where a pharmacy‐based intervention was compared with treatment as usual, waiting list, or an alternative intervention in the management of depression in adults over 16 years of age. Eligible studies had to report at least one of the following outcomes at any time point: depression symptom change, acceptability of the intervention, diagnosis of depression, non‐adherence to medication, frequency of primary care appointments, quality of life, social functioning, or adverse events.  DATA COLLECTION AND ANALYSIS: Two authors independently, and in duplicate, conducted all stages of study selection, data extraction, and quality assessment (including GRADE). We discussed disagreements within the team until we reached consensus. Where data did not allow meta‐analyses, we synthesised results narratively.  MAIN RESULTS: Twelve studies (2215 participants) met the inclusion criteria and compared pharmacy‐based management with treatment as usual. Two studies (291 participants) also included an active control (both used patient information leaflets providing information about the prescribed antidepressant). Neither of these studies reported depression symptom change. A narrative synthesis of results on acceptability of the intervention was inconclusive, with one study reporting better acceptability of pharmacy‐based management and the other better acceptability of the active control. One study reported that participants in the pharmacy‐based management group had better medication adherence than the control participants. One study reported adverse events with no difference between groups. The studies reported no other outcomes. Meta‐analyses comparing pharmacy‐based management with treatment as usual showed no evidence of a difference in the effect of the intervention on depression symptom change (dichotomous data; improvement in symptoms yes/no: risk ratio (RR), 0.95, 95% confidence interval (CI) 0.86 to 1.05; 4 RCTs, 475 participants; moderate‐quality evidence; continuous data: standard mean difference (SMD) ‐0.04, 95% CI ‐0.19 to 0.10; 5 RCTs, 718 participants; high‐certainty evidence), or acceptability of the intervention (RR 1.09, 95% CI 0.81 to 1.45; 12 RCTs, 2072 participants; moderate‐certainty evidence). The risk of non‐adherence was reduced in participants receiving pharmacy‐based management (RR 0.73, 95% CI 0.61 to 0.87; 6 RCTs, 911 participants; high‐certainty evidence). We were unable to meta‐analyse data on diagnosis of depression, frequency of primary care appointments, quality of life, or social functioning. AUTHORS' CONCLUSIONS: We found no evidence of a difference between pharmacy‐based management for depression in adults compared with treatment as usual in facilitating depression symptom change. Based on numbers of participants leaving the trials early, there may be no difference in acceptability between pharmacy‐based management and controls. However, there was uncertainty due to the low‐certainty evidence.